Trial by Jury : the Seventh Amendment and Anglo-American Special Juries. - Oldham, James (NYU Press, 2006)
While the right to be judged by one's peers in a court of law appears to be a hallmark of American law, protected in civil cases by the Seventh Amendment to the Constitution, the civil jury is actually an import from England. Legal historian James Oldham assembles a mix of his signature essays and new work on the history of jury trial, tracing how trial by jury was transplanted to America and preserved in the Constitution. Trial by Jury begins with a rigorous examination of English civil jury practices in the late eighteenth century, including how judges determined one's right to trial by jury.